Behind the History and Cultural Value of The Kusmala Inscription at The Airlangga Museum Kediri - Hartatik, Rista; Ahmad Ruslan; Sri Utami; Afan Faizin; Haerussaleh (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
Culture is all the results of human work, feelings and creations, namely the entire complex way of life, including knowledge, belief, art, morals, customary law and all other abilities and habits acquired by humans as members of society. One of the cultural relics is the Kusmala inscription at the Airlangga Kediri Museum. Philology can be interpreted as love of words or it can also be a love of speaking, speaking with arguments. That is the reason why philologists always play around and like words and texts. This research is qualitative research. This research aims to examine the cultural values of the Kusmala inscription. Data collection was carried out using test and interview methods. This research aims to analyze the contents of the Kusmala inscription, as for the informant named Novi BMW. Research data analysis is descriptive. The results of this research discuss cultural values, as well as the meaning contained in the Kusmala inscription